365 toddler activities that inspire creativity: games, projects, and pastimes that encourage a child's learning and imagination - Levine, Joni (Advantage Quest Sdn. Bhd., 2012)
Features 365 activities for toddlers, including games, art projects, and songs, that are intended to foster creativity, stimulate cognitive development, and encourage inventiveness.